“When am I going to stop taking the drug?” Enablers, barriers and processes of disclosure of HIV status by caregivers to adolescents in a rural district in Zambia - Mweemba, Mable (BMC Public Health, 2015)
BACKGROUND: Disclosure of adolescents’ own HIV status by caregivers is not only challenging but low. The reasons for this remain unclear despite efforts to examine and seek to understand disclosure patterns or factors that may either facilitate or inhibit this disclosure. This study explored the enablers, barriers and processes of disclosure of HIV status to adolescents by their caregivers in Kafue district of Zambia. METHODS: A case study method was used to understand factors that facilitate or inhibit caregiver’s ability to disclose the HIV status of adolescents aged 10–15 years. Data collected through in-depth interviews with 30 caregivers as well as 6 key informants were analysed using thematic analysis. RESULTS: Overall, 17 out of 30 (56.7 %) caregivers had informed the adolescents about their HIV status. Reasons for disclosing of the HIV status included inquiries by adolescents as to why they were taking medication, threats by adolescents not to take HIV medication, desire to promote treatment self-efficacy amongst adolescents as well as facilitating adoption of safe sexual behaviour among adolescents. The disclosure processes were conducted either at the home or at the clinic. Enabling factors for HIV disclosure were adolescents’ knowledge of HIV and caregivers’ knowledge of and experience with HIV programs. Barriers to disclosure of HIV status included fear of psychological trauma for the adolescents, perceived inability of adolescents to keep their HIV status confidential which could attract HIV stigmatisation for the family, and caregivers’, fear of being blamed by the adolescents for the infection, limited disclosure skills by caregivers as well as negative attitude by some HIV counsellors. CONCLUSIONS: Despite challenges associated with disclosure of adolescents’ own HIV status by caregivers, environments that facilitate this process exist and can be strengthened. Promoting HIV disclosure requires in-depth and context-specific understanding of the factors that enable and undermine this process. Limitations in this understanding may have played critical roles in past strategic implementation of locally driven and relevant interventions to improve disclosure of HIV status by caregivers to adolescents in Zambia.